A neutral-point voltage balance control method for 3L-NPC converters - Wang, Jun (Frontiers in Energy Research, 2025)
The inherent problem of neutral-point potential imbalance in three-level neutral-point-clamped (3L-NPC) converters increases the risk of overvoltage in switching devices, causes increased output harmonic content, and seriously affects the performance and safe operation of the converters. To achieve neutral-point voltage balance control, this article proposes a neutral-point voltage balance control method based on zero-sequence component injection. The proposed method has the advantage of low computational complexity and can achieve balance control of neutral-point potential under various operation conditions. Finally, the experimental results validated the correctness and effectiveness of the presented method.